William Stillman: championing Crispi in late Victorian Britain. Issue 4 (28th September 2017) - Laven, David
Abstract : Christopher Duggan made extensive use of the correspondence of the American Times journalist William James Stillman in writing his important biography of Francesco Crispi. This article focuses on Stillman's published works that deal with the Italian statesman, principally his 1898 history of Italy since 1815, the first and only English-language biography of Crispi until Duggan's, and the journalist's own autobiography. It argues that, despite Stillman's much vaunted love for Italy, he in fact despised most Italians, and saw in Crispi's virtues a rejection of typical Italian conduct. While Stillman was extreme but not altogether unusual among British and American commentators on Italy in his passionate support for Crispi, his contempt for Italians was surprisingly widespread among late Victorian observers of the new nation. Italian summary: Nello scrivere la ricca biografia di Francesco Crispi, Christopher Duggan fa largo uso della corrispondenza del giornalista americano del Times, William James Stillman. L'articolo è incentrato su quanto Stillman ha scritto sull'uomo di governo italiano, specie nella sua storia di Italia dal 1815 edita nel 1898, in quella che è stata la prima ed unica biografia di Crispi in inglese prima di quella di Duggan, e nella stessa autobiografia del giornalista. Nell'articolo si sostiene che, nonostante il decantato amore di Stillman per l'Italia, questi fondamentalmente disprezzava la maggior parte degli italiani e interpretava le virtù di Crispi come un rifiuto della tipica condotta italiana. Mentre l'estremismo di Stillman nel sostenere Crispi non era affatto inusuale tra i commentatori inglesi e americani, la sua denigrazione degli italiani risultò sorprendentemente diffusa tra gli osservatori vittoriani della nuova nazione.